Peningkatan Penguatan Branding dan Transparansi Melalui Pengembangan Sistem Informasi Website - Supriadi, Sudawan; Wahyuni, Sri; Siregar, Dwi Rayana; Ulfah, Fadilla; Santoso, Ridwan (Universitas Negeri Gorontalo, 2025)
Strengthening branding and transparency is a strategic step for the University of Jambi Economics Education Study Program to increase competitiveness and public trust. In the digital era, the development of informative, interactive, and responsive websites is an urgent need to strengthen the image of the institution, attract prospective students, and build stakeholder loyalty. This service activity aims to design and develop a website-based information system that is user-friendly and transparent. The methods used include needs analysis, modern design development, internal training, and socialization to the academic community. The results show that the website developed is able to improve data accessibility, provide an optimal user experience, and present the latest information in real-time. This has an impact on improving academic reputation, user trust, and relationships with stakeholders. The integration of digital technology is a strategic model in building trust and credibility in a competitive higher education environment.